A nonlinear sliding mode observer for the estimation of temperature distribution in a planar solid oxide fuel cell. (5th January 2015) - Cheng, Huan; Li, Xi; Jiang, Jianhua; Deng, Zhonghua; Yang, Jie; Li, Jian
Abstract: Compliance to certain temperature constraints is essential for the long life and stable operation of solid oxide fuel cells (SOFCs). However, it is difficult and costly to measure the temperature inside a high temperature, well-sealed cell directly. A nonlinear sliding mode observer has been designed in this paper for estimating the temperature distribution in a hydrogen fed SOFC stack. The observer design is based on a finite-volume parameter SOFC model, which is simplified by quasi-static mass balance assumption. In the observer design, a decoupling pole placement method that applies to multi-timescale systems is proposed to obtain a suitable observer gain. And a quasi-sliding mode control method is adopted to eliminate the chatter caused by the discontinuous control actions of sliding mode control. Theoretical analysis and simulation results are presented to prove the convergence and good performance of the designed observer for estimating the temperature distribution in a SOFC stack during steady-state and transient operation. Highlights: An observer is designed for estimating temperature distribution in SOFC stack. The convergence of observer is proved by theoretical analysis and simulation. A pole placement method that applies to multi-timescale systems is proposed. Quasi-sliding mode control is used to eliminate the chattering on sliding mode.